Effect of low-protein diet on kidney function and nutrition in nephropathy: A systematic review and meta-analysis of randomized controlled trials. Issue 9 (September 2020) - Yue, Hao; Zhou, Pengcheng; Xu, Zhixiang; Liu, Lina; Zong, Aizhen; Qiu, Bin; Liu, Wei; Jia, Min; Du, Fangling; Xu, Tongcheng
Summary: Background: The effects of low-protein diet (LPD) on kidney function and nutrition in nephropathy are so far unclear. Objective: To investigate the effect of LPD on kidney function and nutrition. Data sources: PubMed, Embase and Cochrane library up to January 2019 and references of retrieved relevant articles. Result: Twenty-nine studies with 1784 individuals in the LPD arm and 1782 individuals in the normal protein diet were identified. Compared with normal protein diet, LPD significantly reduced BUN (WMD -20.756 mg/dl; 95% CI: −33.969 to −7.544 mg/dl; P = 0.002), UREA (WMD -1.400 g/24 h; 95% CI: −1.713 to −1.088 mmol/L; P < 0.001), proteinuria (WMD -0.416 g/24 h; 95% CI: −0.715 to −0.117 g/24 h; P = 0.006), body weight (WMD -2.757 kg; 95% CI: −3.890 to 1.623 kg; P < 0.001) and BMI (WMD -0.646 kg/m 2 ; 95% CI: −1.068 to −0.223 kg/m 2 ; P = 0.003). Dose–response analysis showed that reduction of protein intake by 0.1 g/kg/d was associated with a 0.68009 kg, 0.08771 kg/m 2, 0.27147 g/L and 0.00309 g/24 hS reduction in body weight, BMI, ALB and Proteinuria, associated with a 0.135289 ml/min/1.73 m 2 increase in GFR. The effects of LPD were more obvious on aged, obesity, moderate or severe renal impairment and DN patients. Conclusion: Low-protein diet was significantly associated with improvement of nephropathy, but LPD increases the risk of malnutrition such as BMI. The present meta-analysis provides evidence that LPD was associated with malnutrition, and high-quality RCTs with multi-center and large simple-size should be performed to confirm the present findings.